2020
DOI: 10.1101/2020.03.05.20031450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of new Mycobacterium leprae subtype in Bangladesh by genomic characterization to explore transmission patterns

Abstract: Mycobacterium leprae, the causative agent of leprosy, is an unculturable bacterium with a considerably reduced genome (3.27 Mb) compared to homologues mycobacteria from the same ancestry. M. leprae transmission is suggested to occur through aerosols but the exact mechanisms of infection remains unclear. In 2001, the genome of M. leprae was first described and subsequently four genotypes (1-4) and 16 subtypes (A-P) were identified providing means to study global transmission patterns for leprosy. We investigate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…The HCs diagnosed with leprosy at intake (DevLep) were not evenly distributed over the different households: in 14 households none of the HCs had developed leprosy, whereas in the other 17 households, 9-42% suffered from leprosy (Figure 1). Applying previous results on the presence of M. leprae DNA (25), indicated that in 10 households M. leprae DNA was not detected in any of the HCs in NS and in 13 households all HCs were negative in the SSS. Of the households where M. leprae DNA was detected, percentages of colonization varied from 7 to 100% (NS) and for infection from 10 to 66% (SSS; Figure 1).…”
Section: Leprae Dna In Nasal Swabs/slit-skin Smears and The Occurrmentioning
confidence: 50%
See 4 more Smart Citations
“…The HCs diagnosed with leprosy at intake (DevLep) were not evenly distributed over the different households: in 14 households none of the HCs had developed leprosy, whereas in the other 17 households, 9-42% suffered from leprosy (Figure 1). Applying previous results on the presence of M. leprae DNA (25), indicated that in 10 households M. leprae DNA was not detected in any of the HCs in NS and in 13 households all HCs were negative in the SSS. Of the households where M. leprae DNA was detected, percentages of colonization varied from 7 to 100% (NS) and for infection from 10 to 66% (SSS; Figure 1).…”
Section: Leprae Dna In Nasal Swabs/slit-skin Smears and The Occurrmentioning
confidence: 50%
“…The cohort used in this study originates from four districts in Bangladesh (Nilphamari, Rangpur, Panchagar, and Thakurgaon) and has been extensively described previously (25). The prevalence of leprosy in these districts was 0.9 per 10,000 and the new case detection rate 1.18 per 10,000 (Rural health program, the leprosy mission Bangladesh, yearly district activity report 2018).…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations